Collective action, mobility, and shared struggles: how the so-called model minority can come to deny the myth. Issue 2 (3rd March 2016) - Dhingra, Pawan
Abstract : The model minority remains one of the most durable images assigned to immigrant groups despite ample critiques of it. Those persons considered to be a model minority often promulgate the myth themselves. Common arguments against the stereotype do not effectively speak to these people. In this article I demonstrate the disconnect between the critiques of the stereotype and the views of Indian American professionals, a group widely considered to be a model minority. I then offer an alternative approach to dismantling the stereotype that can resonate more with those invested in it. This approach highlights groups' history of collective action in response to racialised and class obstacles. Three case studies illustrate this approach: study of Indian American motel owners, of physicians, and of taxi drivers. Taxi drivers are thought to be on the opposite end of the model minority binary than doctors and successful motel owners. The case studies highlight the grassroots activism shared by all three groups.